2008
DOI: 10.1111/j.1600-0838.2007.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pediatric freestyle and Greco‐Roman wrestling injuries sustained during a 2006 US national tournament

Abstract: The purpose of this study was to compare the epidemiology of freestyle and Greco-Roman wrestling injuries sustained during a 2006 United States (US) national tournament. A prospective injury surveillance study was conducted at the US 2006 ASICS/Vaughan Cadet and Junior National Championships. There were 83 freestyle- and 55 Greco-Roman-related injuries sustained, with the rate of injury per 1000 athlete-matches higher in freestyle (7.0) compared with Greco-Roman (4.6) wrestling [Rate ratio (RR)=1.51, 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 24 publications
2
22
0
5
Order By: Relevance
“…Compared with GR wrestling, there was a greater proportion of knee injuries in FS wrestling as was the case in our study also (18). …”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Compared with GR wrestling, there was a greater proportion of knee injuries in FS wrestling as was the case in our study also (18). …”
Section: Discussionsupporting
confidence: 69%
“…FS fractures were most frequently to the upper extremity (40.0%). GR fractures were to the head/face/neck (40.0%) (18). A study revealed that Olympic-level FS wrestlers had a higher risk of injuries compared with GR wrestlers (6).…”
Section: Discussionmentioning
confidence: 99%
“…During a throwing, the defender wrestler is being pulled up toward the shoulders of the opponent, then thrown on the mat with a high speed, where the wrestler may be stricken with his/her head or shoulders. Although throwing the opponent is allowed in freestyle wrestling, this event rarely occurs, because the offender can impede throwing by grasping offenders' feet [18].…”
Section: Discussionmentioning
confidence: 99%
“…This was a retrospective cross-sectional study. The statistical population consisted of male Greco-Roman and freestyle wrestlers (N=86; age [15][16][17][18][19][20] in Guilan Province, Iran. The study participants had a history of at least two continual years of wrestling training for 3 weekly sessions as well as participating in national and international competitions.…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] By design, hospitalbased ED injury surveillance systems, such as the National Electronic Injury Surveillance System (NEISS), collect information only on injured individuals. Such surveillance systems provide useful descriptive information about severe injury patterns, such as who was injured, what types of injuries occurred, what was happening at the time of injury, and the type of care provided for that injury.…”
mentioning
confidence: 99%